Optimizing Deep Learning-Based STEM Instruction with PhET Simulations to Improve Science Outcomes - Nur Iftitah; Ratih Ulfah R. Syarif; Isma Ina Daud; Siti Irmawati (Berkala Ilmiah Pendidikan Fisika, 2026)
This study aims to optimize the implementation of deep learning–based instruction integrated with a STEM approach and supported by PhET Interactive Simulations to improve students’ science learning outcomes at MTs Hingalalamengi. In line with the demands of 21st-century education, the learning process emphasizes not only superficial concept mastery but also deeper understanding, critical thinking, problem-solving skills, and the ability to relate scientific concepts to real-life contexts. This study employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. Measurements were conducted before and after the implementation to determine the effectiveness of the instructional strategy. The learning process was designed by integrating STEM principles with interactive PhET simulations, enabling students to actively engage in virtual experiments, inquiry-based exploration, and collaborative problem-solving activities. The results indicate a significant improvement in students’ learning outcomes, as shown by higher posttest scores compared to pretest scores. In addition, the use of interactive simulations increased students’ engagement and participation during the learning process. Students became more active in exploring concepts, conducting virtual experiments, and developing their critical thinking skills. The integration of deep learning, STEM approaches, and digital simulation media proved to create a more meaningful and student-centered learning environment. Therefore, this approach is recommended as an innovative instructional strategy to enhance the quality of science education, particularly in madrasah contexts.